Promoting multi-purpose uses and competitiveness of the coconut: Proceedings of a workshop - 26-29 September 1996, Chumphon, Thailand - Batugal, P.A.; Ramanatha Rao, V.; Bong, C.; International Coconut Genetic Resources Network (1998)
The Coconut Genetic Resources Network (COGENT) decided to hold a workshop to discuss alternative uses for coconut which can help increase the competitiveness of the coconut. Researchers from 12 countries who are working on these new alternative coconut products were invited to present their research findings at this workshop. The workshop was held on 26-29 September 1996 in Chumphon, Thailand. The proceedings of this workshop will be useful for researchers, coconut farmers and perhaps even business entrepreneurs to understand the opportunities that exist in producing new high-profit coconut products. On behalf of IPGRI, I would like to thank the Chumphon Horticultural Research Centre of the Department of Agriculture, Thailand for hosting and funding the workshop and IFAD, ADB, BUROTROP, Technical Centre for Agriculture and Rural Co-operation (CTA) for their funding support. We are also very glad that IFAD has subsequently funded the recommendations of this workshop by supporting a project entitled ”Sustainable use of coconut genetic resources to enhance the incomes and nutrition of smallholders in the Asia-Pacific region”. The project will test and pilot the above opportunities and strategies in 13 countries to develop the basis for an expanded and more sustainable project on multi-purpose uses of the coconut.